2010
DOI: 10.1152/ajpregu.00333.2009
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress downregulates endothelin receptor expression and enhances acute stress-mediated blood pressure responses in adult rats

Abstract: We hypothesized that early life stress enhances endothelin (ET-1)-dependent acute stress responses in adulthood. We utilized a unique rat model, wildtype (WT) and ETB receptor-deficient spotting lethal (sl/sl) rats, as well as pharmacological blockade of ET receptors, in a model of early life stress, maternal separation (MS). MS was performed in male WT and sl/sl rats 3 h/day from day 2 to 14 of life. Acute air jet stress (AJS)-induced responses (elevation in blood pressure, plasma corticosterone, and plasma E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 53 publications
5
48
0
Order By: Relevance
“…Consistent with prior studies in humans and rats,2, 11, 12, 13, 14, 15, 16, 20, 21 flox mice exhibited a significant increase in plasma ET‐1 in response to CSS, whereas VEETKO mice exhibited no change in plasma ET‐1 following CSS. We found that pulmonary ET receptor expression and affinity are similar in VEETKO and flox mice, suggesting no differences in ET‐1 clearance capacity in VEETKO and flox mice.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with prior studies in humans and rats,2, 11, 12, 13, 14, 15, 16, 20, 21 flox mice exhibited a significant increase in plasma ET‐1 in response to CSS, whereas VEETKO mice exhibited no change in plasma ET‐1 following CSS. We found that pulmonary ET receptor expression and affinity are similar in VEETKO and flox mice, suggesting no differences in ET‐1 clearance capacity in VEETKO and flox mice.…”
Section: Discussionsupporting
confidence: 88%
“…D'Angelo et al found that ABT‐627 potentiates the pressor response to air jet stress in ET B receptor–deficient rats and transgenic controls on a high‐salt diet50 and in Dahl salt‐resistant, but not Dahl salt‐sensitive, rats,51 suggesting that the ET A receptor may function to attenuate sympathetic responses differentially in these rat strains. More important, the CSS paradigm is distinct from restraint air jet stress in that CSS elicits a prolonged pressor response, for >1 hour, and restraint air jet stress produces a pressor response that dissipates in minutes 21, 46. Together, these studies suggest a complex role of the ET A receptor in the pressor response to acute psychosocial stress paradigms.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to present data, and data in the literature, we retain that at least three different mechanisms can concur in producing functional artery alteration: (1) post-natal handling reduces endothelial nitric oxide synthase buffering capacity, thus sensitizing adult rodents to angiotensin II-induced hypertension [20][21][22]33]; (2) hyperglycemia contributes to cardiovascular diseases, as confirmed by studies carried out on both diabetic and non-diabetic patients, and on animal models [12,15,19]; (3) elevation of plasma ACTH and corticosterone produces vascular alterations and hypertension, as it was reported following chronic treatment with corticosteroids and with corticotrophin (ACTH and analogues) in adult animals [23,35,36].…”
Section: Discussionsupporting
confidence: 77%
“…Clinical-epidemiological investigations found connection between adverse childhood experiences and the risk for developing metabolic and cardiovascular conditions in the adult age in humans [1,7,27,32]. It has been shown also that postnatal psychological stress models were followed by vascular and renal dysfunction in adult rats [20,33]. It is therefore of importance to have simple, reliable and inexpensive models to study the evolution of "pre-diabetic status" up to the appearance of "complications status", in order to understand etiopathogenetic mechanisms, and to develop drugs useful to prevent or reduce risk of complications.…”
Section: Introductionmentioning
confidence: 98%